Crime and crisis: the conjuncture of social forces in early modern Leiden - Bartlett, Christopher Nathan (2005)
This document is a summary of criminal behavior in the Dutch town of Leiden from the middle sixteenth century until the eighteenth century. The thesis maintains that this crime, and criminal statistics in general, may be used as a criteria by which to judge mass social unrest in Early Modern Europe. This period has been termed an age of crisis by a number of historians who point to economic and political instability. This document argues that this crisis also had a social component with the marked rise in criminal behavior as the main indicator of this.The document details the historiographical arguments behind the crisis. It outlines the recognized components of the crisis in a Pan-European context. It argues against the assertion that Holland escaped the crisis by illustrating the extent of turmoil which Leiden shared with the rest of Europe.The document goes on to provide evidence of a dramatic rise in violent and property crime which occurred at the height of the crisis period. Individual trends for each crime and the apparatus of social control within the town are also illustrated in order to examine their relationship to the general crisis.